2016
DOI: 10.1073/pnas.1600372113
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and intrinsic factors of rifampicin tolerance in mycobacteria

Abstract: Mycobacteria grow and divide asymmetrically, creating variability in growth pole age, growth properties, and antibiotic susceptibilities. Here, we investigate the importance of growth pole age and other growth properties in determining the spectrum of responses of Mycobacterium smegmatis to challenge with rifampicin. We used a combination of live-cell microscopy and modeling to prospectively identify subpopulations with altered rifampicin susceptibility. We found two subpopulations that had increased susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
72
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(77 citation statements)
references
References 24 publications
3
72
0
Order By: Relevance
“…In this and previous studies we used the SSB-GFP reporter to characterize the timing of M. smegmatis DNA replication (Figure 2E) [12, 17]. We found that the frequency and duration of E period correlates positively with birth length (Figure 2E) [7].…”
Section: Resultsmentioning
confidence: 57%
See 4 more Smart Citations
“…In this and previous studies we used the SSB-GFP reporter to characterize the timing of M. smegmatis DNA replication (Figure 2E) [12, 17]. We found that the frequency and duration of E period correlates positively with birth length (Figure 2E) [7].…”
Section: Resultsmentioning
confidence: 57%
“…Using time-lapse microscopy, we observed one to two SSB-GFP foci during DNA replication (“C”) but none during pre- (“B”) and post- (“D”) replication periods (Figure 1H). We and others have observed M. smegmatis subpopulations that begin new rounds of replication after completing the first round but before division [10, 12, 17, 19]. We identified this additional replication period (“E”) in 54% of cells by observing SSB-foci near poles pre-division (Figures 1H, 1I&S1P).…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations